Germplasm resources of three wood plant species enriched with nervonic acid - Xing He; Tian-Quan Lu; Jiang-Ying Li; Ping Mao; Li Zhang; Guo-Wei Zheng; Bo Tian (Plant Diversity, 2022)
Nervonic acid (NA) is a very-long-chain monounsaturated fatty acid with pharmaceutical and nutraceutical functions that plays an important role in treating several neurological disorders. One major source of NA is plant seed oil. Here we report fatty acid profiles of seeds and germplasm diversity of six plant species, including three woody plants with high amounts of NA-enriched seed oil, Malania oleifera, Macaranga adenantha, and M. indica. M. oleifera had the largest seed (average 7.40 g single seed), highest oil content (58.71%), and highest NA level (42.22%). The germplasm diversity of M. oleifera is associated with its habitat but not elevation. Seeds of M. adenantha contained higher NA levels (28.41%) than M. indica (21.77%), but M. indica contained a significantly higher oil content (29.22%) and seed yield. M. adenantha germplasm varied among populations, with one population having seeds with high oil content (22.63%) and NA level (37.78%).Although M. indica grow naturally at a range of elevations, no significant differences were detected between M. indica populations. These results suggest that M. indica and M. oleifera have greater potential as a source of NA, which will contribute to constructing a germplasm resource nursery and establishing a selection and breeding program to improve the development of NA-enriched plants.